Considering land tenure in REDD+ participatory measurement, reporting, and verification: A case study from Indonesia - Felker, M.E.; Bong, I.W.; Depuy Walker H.; Jihadah, L.F. (Public Library of Science, 2017)
Measurement, Reporting, and Verification (MRV) systems are thought to be essential for effective carbon accounting and joint REDD+ carbon, conservation, and social development goals. Community participation in MRV (PMRV) has been shown to be both cost effective and accurate, as well as a method to potentially advance stakeholder empowerment and perceptions of legitimacy. Recognizing land tenure as a long-standing point of tension in REDD+ planning, we argue that its engagement also has a key role to play in developing a legitimate PMRV. Using household surveys, key informant interviews, and participatory mapping exercises, we present three ‘lived’ land tenure contexts in Indonesia to highlight their socially and ecologically situated natures and to consider the role of tenure pluralism in shaping PMRV. We then raise and interrogate three questions for incorporating lived land tenure contexts into a legitimate PMRV system: 1) Who holds the right to conduct PMRV activities?; 2) How are the impacts of PMRV differentially distributed within local communities?; and 3) What is the relationship between tenure security and motivation to participate in PMRV? We conclude with implementation lessons for REDD+ practitioners, including the benefits of collaborative practices, and point to critical areas for further research.